2018
DOI: 10.1111/ddg.13729
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the status of teledermatology in Austria

Abstract: SummaryBackgroundThe use of digital communication media is becoming increasingly important, with the primary aim of improving both treatment quality and patients' quality of life. In an effort to optimize telemedicine in the field of dermatology, we conducted a survey among dermatologists in Austria.MethodsStatistical analysis of a questionnaire that was developed by a working group and sent to 769 Austrian dermatologists.ResultsOverall, 243 dermatologists (132 women/111 men) participated in the survey. Forty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
3
17
0
Order By: Relevance
“…Patients, primary care providers, and dermatologists raised concerns and reported challenges about obtaining reimbursement for teledermatology consultations [ 3 , 37 , 43 45 , 47 , 54 , 56 , 62 ]. Lastly, primary care providers and dermatologists reported concerns with liability and privacy issues (e.g., data security) associated with teledermatology [ 43 , 45 , 47 , 52 , 54 , 55 ]. In contrast, only 3 studies (13%) reported facilitators within this domain, making this domain the least commonly reported facilitator to teledermatology implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients, primary care providers, and dermatologists raised concerns and reported challenges about obtaining reimbursement for teledermatology consultations [ 3 , 37 , 43 45 , 47 , 54 , 56 , 62 ]. Lastly, primary care providers and dermatologists reported concerns with liability and privacy issues (e.g., data security) associated with teledermatology [ 43 , 45 , 47 , 52 , 54 , 55 ]. In contrast, only 3 studies (13%) reported facilitators within this domain, making this domain the least commonly reported facilitator to teledermatology implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Questionnaires (20 studies, 67% of included studies) and interviews (9 studies, 30% of included studies) were the most common methods of data collection. Only three of the thirty studies used a theoretical implementation framework to guide their investigation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Each of the three studies used the technology acceptance model, a model designed to assess individuals' level of acceptance of technology (i.e., teledermatology).…”
Section: Theory/framework Usementioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted in Australia with dermatologists, it was found that the participants thought teledermatology was suitable for use mainly for exchanging views between colleagues and for patient follow‐up and that it could not replace the first consultation 11 …”
Section: Discussionmentioning
confidence: 99%
“…Because a common motivation for implementing teledermatology is to improve patient access to expert dermatologic care, access has components of both reach and effectiveness and it is often difficult to separate these two types of outcomes. While effectiveness includes patient and provider satisfaction [44][45][46], for our purposes, effectiveness is the ability of an intervention to change patient-centric outcomes such as reductions in distance traveled by patients, consult completion times, and improvements in actual and intermediate surrogate measures of patient health outcomes. We also discuss cost-effectiveness, which can affect not only patients but also healthcare organizations and payors.…”
Section: Effectivenessmentioning
confidence: 99%